2021
DOI: 10.1021/acs.joc.1c02446
|View full text |Cite
|
Sign up to set email alerts
|

Benzylic Aroylation of Toluenes Mediated by a LiN(SiMe3)2/Cs+ System

Abstract: Chemoselective deprotonative functionalization of benzylic C–H bonds is challenging, because the arene ring contains multiple aromatic C­(sp2)–H bonds, which can be competitively deprotonated and lead to selectivity issues. Recently it was found that bimetallic [MN­(SiMe3)2 M = Li, Na]/Cs+ combinations exhibit excellent benzylic selectivity. Herein, is reported the first deprotonative addition of toluenes to Weinreb amides mediated by LiN­(SiMe3)2/CsF for the synthesis of a diverse array of 2-arylacetophenones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 78 publications
0
19
0
1
Order By: Relevance
“…Lately, Chirik and co‐workers disclosed deborylative addition of methyl esters to gem ‐diborantes in presence of LiO t Bu [25] . Very recently, Li, Mao, Walsh and co‐workers elegantly disclosed the usage of silyl amides in deprotonation of toluene followed by the addition of N ‐acyl pyrrole amides, [26a] Weinreb amides and simple methyl esters [26b] to yield 1,2‐diphenylethanones. In the realm of benzylic functionalization, Mao, Walsh and co‐workers greatly contributed towards the benzylic C−H bond arylation, [7,27] aminobenzylation [28] and synthesis of indoles by treating 2‐fluorotoluene to benzonitriles [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Lately, Chirik and co‐workers disclosed deborylative addition of methyl esters to gem ‐diborantes in presence of LiO t Bu [25] . Very recently, Li, Mao, Walsh and co‐workers elegantly disclosed the usage of silyl amides in deprotonation of toluene followed by the addition of N ‐acyl pyrrole amides, [26a] Weinreb amides and simple methyl esters [26b] to yield 1,2‐diphenylethanones. In the realm of benzylic functionalization, Mao, Walsh and co‐workers greatly contributed towards the benzylic C−H bond arylation, [7,27] aminobenzylation [28] and synthesis of indoles by treating 2‐fluorotoluene to benzonitriles [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Our team has had a long-standing interest in the impact of main group counterions in altering the course of reactions, 22 which have been attributed to cation–π interactions in some cases. Most recently, in our study of toluene aroylations, 23 we found that N -acyl pyrroles underwent benzylation in the presence of toluene and KN(SiMe 3 ) 2 while the parent N -acyl pyrrole underwent isomerization in the presence of LiN(SiMe 3 ) 2 (Scheme 2C). 24…”
mentioning
confidence: 88%
“…传统上利 用酰胺合成芳基乙酮类化合物, 依赖于 Weinreb 酰胺与 格氏试剂的偶合 [44] . 2021 年, 毛建友课题组 [45] 实现了在 亲电试剂 Weinreb 酰胺或苯甲酸甲酯存在下对甲苯苄位 C(sp 3 )-H 键的功能化(Scheme 27). 该方法以甲苯衍生 物为溶剂, LiN(SiMe 3 ) 2 为碱, 在加入少量 CsF 或 Cs 2 SO 4 情况下与 Weinreb 酰胺或苯甲酸甲酯加成消除, 以一种 简便、经济的方法制备了多种二苯乙酮衍生物(68 examples, 45%~95% yields).…”
Section: C(sp 3 )-H 键芳基化反应unclassified